An overview of hydrogen as a vehicle fuel - H., Fayaz; R., Saidur; N. , Razali; F.R, Anuar; A.R, Saleman; M.R, Islam (ELSEVIER, 2012)
As hydrogen fuel cell vehicles move from manifestation to commercialization, the users expec t safe, convenient and customer-friendly fuelling. Hydrogen quality affects fuel cell stack performance and life time, as well as other factors such as valve operation. In this paper, previous researcher’s development on hydrogen as a possible major fuel of the future has been studied thoroughly .Hydrogen is one of the energy carriers which can replace fossil fuel and can be used as fuel in an internal combustion engines and as a fuel cell in vehicles. To use hydrogen as a fuel of internal combustion engine, engine design should be considered for avoiding abnormal combustion. As a result it can improve engine efficiency, power output and reduce NOx emissions. The emission of fuel cell is low as compared to conventional vehicles but as penalty, fuel cell vehicles need additional space and weight to install the battery and storage tank, thus increases it production cost. The production of hydrogen can be ‘carbon-free’ only if it is generated by employing genuinely carbon-free renewable energy sources. The acceptability of hydrogen technology depends on the knowledge and awareness of the hydrogen benefits towards environment and human life. Recent study shows that people still do not have the sufficient information of hydrogen.